Land of Extinct Volcanoes Geopark – geoeducation for everyone - Słomski, Piotr; Jankowska, Julia; Rozpędowska, Ewelina (Geotourism/Geoturystyka, 2021)
The Kaczawskie Mountains and Foothills – Geopark Land of Extinct Volcanoes is an area with an extremely interesting geological structure and outstanding landscape values. Great geo-diversity makes it possible to prepare a geoeducation offer for practically every recipient – from kids, through adults interested in natural sciences, to natural science students. The characteristics of the Kaczawskie Mountains and Foothills enable one to develop a nationally unique form of geotourism and utilization of local natural resources for various geoeducation programs. Despite the small area of the mentioned region, it is possible to raise topics related to volcanic phenomena, the formation of mountain ranges, climate change and the impact of glaciers on  the relief of the terrain. Educational activity at the Geopark Land of Extinct Volcanoes do not need to be limited only to geological issues, but may also include environmental issues, waste management or even historical topics. However, apart from the very existence of geotourism attractions, equally important are their uniform promotion and dissemination of knowledge about them. This can be done by describing the most important geopoints in the field, e.g. through a network of educational boards or by organizing promotional field trips. This would increase the knowledge about the geological richness of the described region among tourists and residents. The work of the Kaczawskie Association, which is trying to include the Land of Extinct Volcanoes Geopark in the UNESCO World Geopark Network, is currently heading in this direction. The implementation of this initiative will not only increase the interest in natural sciences and the region, but will also allow it to keep its authentic and unique character. Unfortunately, the process of application to the UNESCO GGN, both the development of the geoeducation and geotourism in the region of the Kaczawskie Mountains and Foothills, has been slowed down by the COVID-19 pandemic.